Factors influencing stress among female students in Universiti Malaysia Kelantan (City Campus)/ Hafzal Halim and Naziatul Aziah Mohd Radzi - Halim, Hafzal; Mohd Radzi, Naziatul Aziah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2022)
Stress has affected mental health among people in Malaysia. Stress is a kind of emotional disorder that human often experience, especially among university students in Malaysia and stress can be described as a state or feeling of anxiety, frustration, and demotivate. In addition, stress affects all facets of human life. The objective of this study is to identify the relationship between cyber bullying, education level, and psychosocial behaviour and the level of stress among fourth year female students in University of Malaysia Kelantan, City Campus. Data were gathered from 275 respondents using questionnaire survey. From the analysis, it was validated that cyber-bullying, education as well as psychosocial behaviour significantly influencing stress among respondents. This study is hoped to shed a light on the factors that trigger to stress level and could become the indicator to students, parents as well as adding to a body of knowledge. This study is also expected to add to the existing research on stress which is an important issue and needs to be addressed effectively by various parties.